Assessment of Ocular Surface Disease Status in New Patients Initiating Anti-Glaucoma Medication: A Prospective Study - Thakur, Krishna Kumar; Gupta, Krishna Kant; Mishra, Sumit Kumar; Jha, Nina; Chaudhary, Shivram; Singh, Anjani Kumar (Birat Journal of Health Sciences, 2025)
Introduction: Glaucoma is a chronic progressive optic neuropathy and a leading cause of irreversible blindness. Topical medications are first-line therapy, but preserved formulations, especially those with benzalkonium chloride, can damage the ocular surface, causing discomfort, instability, and poor adherence. Data from Nepal on early ocular surface changes after treatment initiation are limited.Objectives: To evaluate ocular surface disease status in newly diagnosed glaucoma patients initiating topical anti-glaucoma medications over a six-month period.Methods: This prospective cohort study was conducted in the Glaucoma Department of Biratnagar Eye Hospital over 10 months. 98 eyes of 78 patients above 35 years with newly diagnosed primary open-angle glaucoma, normal tension glaucoma, or ocular hypertension were enrolled. Patients with pre-existing ocular surface disease, recent topical therapy, prior ocular surgery, or systemic diseases affecting the ocular surface were excluded. Ocular surface assessment included Ocular Surface Disease Index (OSDI), tear film break-up time (TBUT), Schirmer’s I test, and Oxford grading of corneal/conjunctival staining, recorded at baseline, 1, 3, and 6 months. Medications included timolol, brimonidine, travoprost, dorzolamide, and fixed timolol + brimonidine combinations. Data were analysed using SPSS v26.Results: At baseline, ocular surface parameters were within normal limits. At 6 months, OSDI increased to 30.2 ± 9.1, TBUT declined to 7.1 ± 2.7 sec, Schirmer’s reduced to 10.6 ± 2.9 mm, and staining worsened significantly (p